Modeling the synergistic antibacterial effects of honey characteristics of different botanical origins from the Sahara Desert of Algeria - Laallam, Hadda; Boughediri, Larbi; Bissati, Samia; Menasria, Taha; Mouzaoui, Mohamed S.; Hadjadj, Soumia; Hammoudi, Rokia; Chenchouni, Haroun (Frontiers in Microbiology, 2015)
Background: Honey has multiple therapeutic properties due to its composition with diverse components. Objectives: This study aims to investigate the antimicrobial efficacy of Saharan honeys against bacterial pathogens, the variation of honey floral origins and its physicochemical characteristics. Materials and Methods: The antimicrobial activity of 32 samples of honey collected from the Algerian Sahara Desert was tested on four pathogenic bacteria; Bacillus subtilis, Clostridium perfringens, Escherichia coli and Staphylococcus aureus. The botanical origin of honeys and their physicochemical properties were determined and their combined antibacterial effects were modeled using a generalized linear mixed model (GLMM). Results: Out of the 32 study samples, 14 were monofloral and 18 were multifloral. The pollen density was on average 7.86 × 106 grains/10 g of honey, water content was 14.6%, electrical conductivity was 0.5 μS/cm, pH was 4.38±0 50, hydroxymethylfurfural content was 82 mg/kg of honey, total sugars = 83%, reducing sugars = 71%, and the concentration of proline = 525.5±550.2 mg/kg of honey. GLMM revealed that the antibacterial effect of honey varied significantly between bacteria and floral origins. This effect increased with increasing of water content and reducing sugars in honey, but it significantly decreased with increase of honey electrical conductivity. E. coli was the most sensitive species with an inhibition zone of 10.1±4.7 mm, while C. perfringens was the less sensitive with 3.9±5.4 mm. Honeys dominated by pollen of Fabaceae sp. were most effective with an overall antimicrobial activity equals to 13.5±4.7 mm. Conclusion: Saharan honeys, of certain botanical origins, have physicochemical and pollinic characteristics with relevant potential for antibacterial purposes. This encourages a more comprehensive characterization of honeys with in vivo and in vitro investigations. Keywords: Honey characterization; antibacterial effects; floral origin; inhibition zone; Sahara Desert bioresources; GLMM.